Evaluation of As, Cd, Ni and Se Content of Some Mineral Concrete Agents - Şevik, Hakan; Elajaıl, İbrahim Saleh (Kastamonu University, 2024)
In this study, the variation of arsenic (As), cadmium (Cd), nickel (Ni) and selenium (Se) concentrations in some materials used as concrete admixtures were evaluated. These heavy metals are extremely hazardous elements for both human and other living organisms and the environment. Due to these hazards, they are on the priority pollutant list of both ATSDR and EPA. Study results show that heavy metal concentrations in some additives are at very high levels. As a result of the study, the highest As concentrations were obtained in copper slag, vermiculite and cem III cement, the highest Cd concentrations in crushed stone and copper slag, the highest Ni concentrations in copper slag, wood ash and brick powder, and the highest Se concentrations in blast furnace slag and cem III cement. This may pose a great risk to the health of people working in the industry and the environment.
Keywords: Concrete; additive; heavy metals; Environmental Pollution and Prevention; Çevre Kirliliği ve Önlenmesi; 13. Climate action; 6. Clean water; 12. Responsible consumption